Analysis of Adverse Drug Reactions caused by antipsychotic drugs in a Mexican health institute: Análisis de Reacciones Adversas a Medicamentos por fármacos antipsicóticos en un instituto de salud mexicano - Rojas-Valladares, Erick (2024)
Introduction: Adverse Drug Reactions (ADRs) are unwanted clinical or laboratory manifestations that are related to drug use. ADRs are common and are associated with significant risk of morbidity, mortality and hospital admissions. Antipsychotics have a reduced therapeutic window, and have been related to the manifestation of a variety of ADRs. Objective: To evaluate the pattern of ADRs due to antipsychotic drugs detected in patients treated at the Ramón de la Fuente Muñiz National Institute of Psychiatry between December 2021 and May 2022. Methods: Observational, descriptive, prospective and cross-sectional study of a series of cases. The seriousness, severity, and quality of the information in the notification of the ADRs were defined in accordance with “NOM-220-SSA1-2016, Installation and Operation of Pharmacovigilance”, while causality was determined using the Naranjo algorithm. Results: The incidence of ADRs was 59%, with one or more ADRs detected in 52 of the 88 patients who were receiving antipsychotic treatment during the study period. Forty-five percent of the ADRs had "probable" causality and 55% "possible"; only three ADRs were classified as serious as they prolonged the hospital stay and endangered the patient's life. Conclusions: The ADRs of the gastrointestinal and endocrine systems were the most incidental, with hyperprolactinemia being the most frequent. Olanzapine and clozapine were the medications that caused the most ADRs. It is recommended to promote the culture of notification and follow-up of ADRs caused by antipsychotic drugs.